Topological Properties of Periodic Components of Structurally Stable Diffeomorphisms - Vlasenko, I. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider periodic components of structurally stable diffeomorphisms on two-dimensional manifolds. We study properties of these components and give a topological description of their boundaries.